THE EFFECTIVENESS OF PRESENTATION, PRACTICE, PRODUCTION (PPP) METHOD IN DEVELOPING STUDENTS’ SPEAKING SKILL AT MA AL-KHAIRAAT LUWUK - Nurhaida Lakuana; Sintiya Siojam (BABASAL English Education Journal, 2020)
This research aims to find out the effectiveness of the Presentation, Practice, Production (PPP) method in developing students’ speaking skills at MA Al-khairaat luwuk. This research employed a pre-experimental research design involving one-group pre-test–post-test design. The independent variable of this research was Presentation, Practice, Production (PPP) method and the dependent variable was students’ speaking skills. The research population was eleventh-grade students of MA Al-khairaat Luwuk. There were two classes in this population namely one religion class consisted of 20 students and one science class consisted of 12 students. The sample of this research was the religion class. The test included pre-test and post-test. Data were analyzed statistically. Having analyzed the data, the result revealed that the t-counted was (9.87) with a degree of freedom 19 and a significance level of 0.05, t-table was (1.72913). Therefore, the t-test result was higher than the t-table. It means that the hypothesis was accepted. In conclusion, the result showed that there was a significant effect using the Presentation, Practice, Production (PPP) method in developing students’ speaking skills at MA Al-khairaat Luwuk.